The factors that contribute to absenteeism among employees at Kamaruzaman Agency / Suhaimy Mohd - Mohd, Suhaimy (2010)
Absenteeism constitute one of the problem that occur in organization which affect not only the employees performance, but also the performance of the organization itself in term of productivity, production as well as services. The main objective of this research is to determine the factors that contribute to absenteeism at the Kamaruzaman Agency, Melaka. Besides, researcher also identifies the main factors which affect absenteeism plus the relationship between the factors towards absenteeism. The factors are working environment, payment, job itself and supervision. Researcher used questionnaire as a main instrumental in data collection method. Next, data that have been collected, will be analyzed through frequency, percentage, mean and Pearson Correlation. In general, the results of this research show that factor job itself is the most influence towards absenteeism. This followed by the factors of working environment, supervision and payment.